The Effect Of Audiovisual Feedback On The Learning Of Passing And Receiving Skills Among Football Players Less Than 14 Years Old - Belkacemi , Brahim; Hadjidj , Mouloud; Sami, Abdelkader (sports creativity, 2025)
The study aims to identify the effect of audiovisual feedback on learning passing and receiving skills among football players less than 14 years old. For this purpose, we used the experimental method. A training program with audio-visual feedback based on the learning of the two scrolling and receiving skills was also applied to a sample of 30 players divided into two deliberately selected control groups (15 players) and experimental groups (15 players). After the statistical collection and processing of the results, statistically significant differences have been found for the exprimental group, which means that the audiovisual feedback program has a positive effect on the learning of the pass and receive skills. On this basis, the study recommended that this type of feedback be used to teach basic football skills